Does Video Recording effect on Students Fluency and Accuracy in Speaking? : an experimental Study - muhammad nija fariqi (Graduate Program, University of Islam Malang, 2020)
This study focused on investigating of the effectiveness of using video recording on students' fluency and accuracy in speaking of male and female students. In addition, researchers also want to know the differences in the value of fluency and accuracy in speaking of male and female students.The study was conducted on march 2019 at SMP Plus Darussalam Blokagung Banyuwangi. It employed experimental pre-experimental study. It involved 30 students of one group, 15 male students and 15 female students. The first step was administering a pretest then applying the experimental treatment teaching speaking by using video recording and the last step was administering a post-test. The data were obtained by using a pre-test and a post -test. Before the treatment the reseacher gave the pre-test and in the end of step is the post-test after the treatment. descriptive statistics were used to analyze the pre-test and post-test of data. The result of the data showed that were a significant difference score of male and female students of fluency and accuracy in speaking before being taught by using video recording and after being taught by using video recording. By comparing the t-value and t-tabel of one tailed test that the researcher has got calculation t count is bigger than t-tabel, for male students’ fluency was (9.025>2.624 p = 0.01), for male students’ accuracy was (2.256>1.761p = 0.05), for female students’ fluency was (12.475>2.624 p = 0.01), For female students’ accuracy was (16.000>2.624 p = 0.01). So, it was concluded that the hypothesis of this study were accepted. It means that video recording significantly improve students’fluency and accuracy of male and female students in speaking skill after being taught by using video recording.For comperasion of fluency of male and female students. The researcher got the the value of sig. (2tailed) was 0.481 biger than 0.05. It was concluded that there was no significant difference between the value of fluency results in male and female groups after being taught by video recording. For comperasion of accuracy of male and female students. The researcher got the the value of sig. (2tailed) was 0.000 smaller than 0.05. it was concluded that there was significant difference between the value of accuracy results in male and female groups after being taught by video recording.